2022
DOI: 10.3389/fendo.2022.974254
|View full text |Cite
|
Sign up to set email alerts
|

Multiscale entropy and small-world network analysis in rs-fMRI — new tools to evaluate early basal ganglia dysfunction in diabetic peripheral neuropathy

Abstract: ObjectiveThe risk of falling increases in diabetic peripheral neuropathy (DPN) patients. As a central part, Basal ganglia play an important role in motor and balance control, but whether its involvement in DPN is unclear.MethodsTen patients with confirmed DPN, ten diabetes patients without DPN, and ten healthy age-matched controls(HC) were recruited to undergo magnetic resonance imaging(MRI) to assess brain structure and zone adaptability. Multiscale entropy and small-world network analysis were then used to a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 46 publications
0
1
0
Order By: Relevance
“…Previous studies have demonstrated reduced gray matter volume ( Zhang et al, 2020 ) and cortical thickness ( Selvarajah et al, 2019 ) in the precentral region in patients with diabetic neuropathy. A small-world network analysis showed decreased nodal importance in the precentral gyrus in patients with diabetic neuropathy ( Yuan et al, 2022 ), suggesting that diabetic neuropathy is closely related to abnormal central sensorimotor function. In this study, the T2DM group included 27 patients with peripheral neuropathy, which may have been responsible for the abnormal structural topological properties in the precentral region.…”
Section: Discussionmentioning
confidence: 99%
“…Previous studies have demonstrated reduced gray matter volume ( Zhang et al, 2020 ) and cortical thickness ( Selvarajah et al, 2019 ) in the precentral region in patients with diabetic neuropathy. A small-world network analysis showed decreased nodal importance in the precentral gyrus in patients with diabetic neuropathy ( Yuan et al, 2022 ), suggesting that diabetic neuropathy is closely related to abnormal central sensorimotor function. In this study, the T2DM group included 27 patients with peripheral neuropathy, which may have been responsible for the abnormal structural topological properties in the precentral region.…”
Section: Discussionmentioning
confidence: 99%